Description of Non-Communicable Diseases Among Prospective Hajj Pilgrims in Ternate City in 2023 - Dauf Wahid; Suharto Suharto; Tutik Lestari (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Hajj is one of the five pillars of Islam that is performed by Muslims. This study aims to provide an overview of non-communicable diseases such as hypertension, diabetes, and obesity among prospective hajj pilgrims in Ternate City in 2023. The qualitative descriptive research method describes the health conditions of prospective hajj pilgrims in the city of Ternate. The population of all prospective hajj pilgrims in the city of Ternate in 2023 is 286 people. The sample for this research was taken from the entire population using total sampling. The research results show that the most common disease among female prospective hajj pilgrims is hypertension, with 58 people (59.7%), in the age group of 50 to 70 years, 55 people (56.7%), and most of them live in the working area of BLUD Puskesmas Kalumata, 25 people (25.7%). The most common disease among women was diabetes mellitus, with 31 people (63.2%), and most of them lived in the working area of BLUD Puskesmas Kalumata, with 19 people (38.7%), and the most common condition was obesity among women, with 26 people (78.7%). It is hoped that healthcare facilities and the Hajj organizers will more closely monitor prospective pilgrims who will perform the Hajj next year. Specifically, it is hoped that healthcare facilities and Hajj organizers will be able to control the lifestyle and health status of the prospective Hajj pilgrims.